Regulatory Role of N6-Methyladenosine in Longissimus Dorsi Development in Yak - Ma, Xiaoming; La, Yongfu; Bao, Pengjia; Chu, Min; Guo, Xian; Wu, Xiaoyun; Pei, Jie; Ding, Xuezhi; Liang, Chunnian; Yan, Ping (Frontiers in Veterinary Science, 2022)
N6-methyladenine (m6A) RNA undergoes epigenetic modification, which is the most extensive intermediate chemical modification in mRNA. Although this modification occurs in all living organisms, it is the most widely studied among mammals. However, to date, no study has investigated the m6A transcriptome-wide map of yak and its potential biological functions in muscle development. In this study, the differences of m6A methylation and gene expression in yak muscle development belonging to three age groups, namely 3 years (group A), 6 months (group M), and 90-day-old fetuses (group E), were determined by using methylated RNA immunoprecipitation sequencing (MeRIP-Seq) and RNA sequencing (RNA-Seq). In these three groups, a total of 6,278 (A), 9,298 (E), and 9,584 (M) m6A peaks were identified, with average densities between 1.02 and 2.01. m6A peaks were mostly enriched in the stop codon, 3′ untranslated region (UTR) region, and inner long exon region with consensus motifs of UGACA. In all the three stages, the m6A peak enrichment level was significantly negatively correlated with mRNA abundance (Pearson's correlation coefficient r = −0.22 to −0.32, p < 10−16). The functional enrichment of genes consistently modified by m6A methylation, particularly those genes that regulate cell differentiation as well as muscle growth and development, was observed at all three stages. Moreover, m6A abundance was negatively associated with gene expression levels, indicating that m6A might play a vital role in modulating gene expression during yak muscle development. This comprehensive map thus provides a solid foundation for determining the potential functional role of m6A RNA modification in yak muscle growth.